Lung development and immune status under chronic LPS exposure in rat pups with and without CD26/DPP4 deficiency - Schmiedl, Andreas; Wagener, Inga; Jungen, Meike; von Hörsten, Stephan; Stephan, Michael (Cell and Tissue Research, 2021)
Dipeptidyl-peptidase IV (CD26), a multifactorial integral type II protein, is expressed in the lungs during development and is involved in inflammation processes. We tested whether daily LPS administration influences the CD26-dependent retardation in morphological lung development and induces alterations in the immune status. Newborn Fischer rats with and without CD26 deficiency were nebulized with 1 µg LPS/2 ml NaCl for 10 min from days postpartum (dpp) 3 to 9. We used stereological methods and fluorescence activated cell sorting (FACS) to determine morphological lung maturation and alterations in the pulmonary leukocyte content on dpp 7, 10, and 14. Daily LPS application did not change the lung volume but resulted in a significant retardation of alveolarization in both substrains proved by significantly lower values of septal surface and volume as well as higher mean free distances in airspaces. Looking at the immune status after LPS exposure compared to controls, a significantly higher percentage of B lymphocytes and decrease of CD4+CD25+ T cells were found in both subtypes, on dpp7 a significantly higher percentage of CD4 T+ cells in CD26+ pups, and a significantly higher percentage of monocytes in CD26− pups. The percentage of T cells was significantly higher in the CD26-deficient group on each dpp. Thus, daily postnatal exposition to low doses of LPS for 1 week resulted in a delay in formation of secondary septa, which remained up to dpp 14 in CD26− pups. The retardation was accompanied by moderate parenchymal inflammation and CD26-dependent changes in the pulmonary immune cell composition.
CRIS-Team Scopus Importer:2021-10-15
Keywords: CD26/DPP4; Immune cells; Lipopolysaccharide (LPS); Lung development; Rat